Activator‐type R2R3‐MYB genes induce a repressor‐type R2R3‐MYB gene to balance anthocyanin and proanthocyanidin accumulation. Issue 4 (13th October 2018) - Zhou, Hui; Lin‐Wang, Kui; Wang, Furong; Espley, Richard V.; Ren, Fei; Zhao, Jianbo; Ogutu, Collins; He, Huaping; Jiang, Quan; Allan, Andrew C.; Han, Yuepeng
Summary: Anthocyanin and proanthocyanidin (PA) accumulation is regulated by both myeloblastosis (MYB) activators and repressors, but little information is available on hierarchical interactions between the positive and negative regulators. Here, we report on a R2R3‐MYB repressor in peach, designated PpMYB18, which acts as a negative regulator of anthocyanin and PA accumulation. PpMYB18 can be activated by both anthocyanin‐ and PA‐related MYB activators, and is expressed both at fruit ripening and juvenile stages when anthocyanins or PAs, respectively, are being synthesized. The PpMYB18 protein competes with MYB activators for binding to basic Helix Loop Helixes (bHLHs), which develops a fine‐tuning regulatory loop to balance PA and anthocyanin accumulation. In addition, the bHLH binding motif in the R3 domain and the C1 and C2 repression motifs in the C‐terminus of PpMYB18 both confer repressive activity of PpMYB18. Our study also demonstrates a modifying negative feedback loop, which prevents cells from excess accumulation of anthocyanin and PAs, and serves as a model for balancing secondary metabolite accumulation at the transcriptional level.